3x-5=7x+23

Simple and best practice solution for 3x-5=7x+23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-5=7x+23 equation:


3x-5=7x+23

We simplify the equation to the form, which is simple to understand
3x-5=7x+23

We move all terms containing x to the left and all other terms to the right.
+3x-7x=+23+5

We simplify left and right side of the equation.
-4x=+28

We divide both sides of the equation by -4 to get x.
x=-7

See similar equations:

| 9r^2+30r+25=0 | | 6x+3-2y-x= | | km=390m | | v^2-v-42=0 | | 12(1.5-x)=18*x | | 7+7x=-(x+4)+(8x-32) | | 1.5x-12=18*x | | -2x/12=9/12 | | 3r+11+7r= | | A^4-15a^2+56=0 | | 7+7x=-(x+4)+8x-32 | | 3x^4+6x^2-72=0 | | 5x^2+3x-15=80 | | -2p^2-4p+3=0 | | 9(7x-8)+8=10x-3 | | 0.5(2c-4)=0.33(6c-30) | | 19.416x^2-108.672x+125.78=0 | | x*3/4*5/6=18 | | 3+3=3+3+3+3+3+3 | | 19.416x^2+108.672x+125.78=0 | | 98x+56y=15000 | | (x-6)/6=(3x)/8 | | 6+(x+3)=x | | -1.6-4x-2x=5x+4.5 | | h=-16t^2+gt+k | | .2(x+5)+4x-19=2x+7-2(3-x) | | 2(x-3)-3(4-2x)+x= | | 3j=81 | | 5x(3+7)=13 | | 6*n=42 | | 48/=4 | | n*11=88 |

Equations solver categories